2015
DOI: 10.3945/ajcn.115.115451
|View full text |Cite
|
Sign up to set email alerts
|

Associations between human milk oligosaccharides and infant body composition in the first 6 mo of life

Abstract: These findings support the hypothesis that differences in HMO composition in mother's milk are associated with infant growth and body composition. This trial was registered at clinicaltrials.gov as NCT02535637.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
197
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(219 citation statements)
references
References 46 publications
12
197
3
7
Order By: Relevance
“…Human milk oligosaccharides may promote slower ponderal growth and lower body fat during infancy by influencing the gut microbiome (37). Moreover, exclusive BF also fosters an anti-inflammatory cytokine milieu that may decrease future risk of obesity (38).…”
Section: Discussionmentioning
confidence: 99%
“…Human milk oligosaccharides may promote slower ponderal growth and lower body fat during infancy by influencing the gut microbiome (37). Moreover, exclusive BF also fosters an anti-inflammatory cytokine milieu that may decrease future risk of obesity (38).…”
Section: Discussionmentioning
confidence: 99%
“…Analytical staff was blinded to the clinical metadata associated with each sample. HMO analysis was performed by high-performance liquid chromatography (HLPC) after fluorescent derivatisation with 2-aminobenzamide (2AB) as previously described 15 16. The non-HMO oligosaccharide raffinose was added to each milk sample as internal standard at the very beginning of sample preparation to allow for absolute quantification.…”
Section: Methodsmentioning
confidence: 99%
“…HMOs are natural prebiotics that serve as an energy source for a diverse array of colonic bacteria and hence shape and sustain the infant gut microbiome. Although studies have shown that the composition, diversity, and abundance of specific HMOs is associated with infant growth and adiposity, 158 the effect of maternal obesity on the diversity of HMOs in milk is poorly understood.…”
Section: Alterations In Neonatal Nutrition and Infant Microbiomementioning
confidence: 99%